2015
DOI: 10.1016/j.jaapos.2015.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal serum insulin-like growth factor i and retinopathy of prematurity

Abstract: INTRODUCTION-Low serum insulin-like growth factor 1 (IGF-1) has been associated with development of severe retinopathy of prematurity (ROP), but no U.S. studies have been reported. We sought to determine the relationship between postnatal serum IGF-1 levels and severe ROP in a racially diverse U.S. cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
(44 reference statements)
0
7
1
Order By: Relevance
“…We are grateful to Doctors Reddy, Patel, and Sinha for their kind comments and interest. 1 It is interesting that their UK study 2 and our Philadelphia study 3 demonstrated similar IGF-1 levels in premature infants, but these levels were different in magnitude from the Swedish cohort. 4 Perhaps this observation is due to the IGF-1 assay used in each study.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…We are grateful to Doctors Reddy, Patel, and Sinha for their kind comments and interest. 1 It is interesting that their UK study 2 and our Philadelphia study 3 demonstrated similar IGF-1 levels in premature infants, but these levels were different in magnitude from the Swedish cohort. 4 Perhaps this observation is due to the IGF-1 assay used in each study.…”
mentioning
confidence: 75%
“…4 Perhaps this observation is due to the IGF-1 assay used in each study. In both the UK and Philadelphia studies, an immunoenzymatic assay was used, 2,3 while in the Swedish study, a radioimmunoassay was used. 4…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…IGF-1 is an anabolic hormone that promotes the development of many types of body tissues including the retinal vasculature. An association has been found between early postnatal decrease in IGF-1 levels and the development of retinopathy of prematurity [14].…”
Section: New Criteria Regarding Risk Factorsmentioning
confidence: 99%
“…After term birth, neonate serum levels of IGF-1 decrease; this change is exacerbated in the setting of preterm birth [63]. Further, premature infants who develop ROP have lower serum levels of IGF-1 at birth compared to age-matched infants without disease, suggesting that low IGF-1 is an independent risk factor for subsequent ROP disease [64][65][66][67]. However, post-natal growth rate proved to be a suitable proxy for IGF-1 levels, and has largely replaced IGF-1 for modeling ROP risk.…”
Section: Preventive Interventions Informed By Rop Molecular Pathogenementioning
confidence: 99%